A note on oblique water entry - Moore, M; Howison, S; Ockendon, J; Oliver, J (2012)
An apparently minor error in Howison, Ockendon & Oliver (J. Eng. Math. 48:321–337, 2004) obscured the fact that the points at which the free surface turns over in the solution of the Wagner model for the oblique impact of a two-dimensional body are directly related to the turnover points in the equivalent normal impact problem. This note corrects some results given in Howison, Ockendon & Oliver (2004) and discusses the implications for the applicability of the Wagner model.